Anticorrosion Inhibition Behavior of Rhus Pentaphylla Fruit Extracts in (1 M) HCl against Carbon Steel and their Chemical Characterization using HPLC‐MS‐ESI. Issue 21 (1st June 2021) - Fadhil, Hajer; Mraihi, Farouk; Zouied, Daoiya; Ayadi, Malika Trabelsi; Cherif, Jamila Kalthoum
Abstract: Phenolic compounds in Tunisian wild Rhus pentaphylla fruits during two maturity stages are identified by LC‐MS‐ESI. The corrosion inhibition efficiency of their extracts was analyzed by the use of polarization curves and electrochemical impedance spectroscopy. The qualitative analysis highlighted the presence of 11 phenolic compounds in total (3 phenolic acids and 8 flavonols) for the un‐ripe stage (S1), 7 compounds (1 phenolic acid and 6 flavonols) have been identified for the fully‐ripe stage (S2). The electrochemical behavior analysis of carbon steel in (1 M) HCl medium showed a maximum inhibition efficiency of 45.49 % was achieved by using 100 ppm of the inhibitor. Polarization studies indicate that the extracts act as a mixed inhibitor. As well, it has been shown that the first stage presents the highest inhibitory efficacy compared to the second. These results confirm the good correlation between the phytochemical composition and corrosion inhibition capacity. Abstract : Phytochemical composition of Tunisian R.pentaphylla fruits during two maturity stages is investigated by LC‐MS. Analysis highlighted the presence of 11 phenolic compounds. Corrosion inhibition efficiency of extracts was analyzed by polarization curves and electrochemical impedance. The extracts act as a mixed inhibitor and the electrochemical behavior analysis of carbon steel in HCl medium showed a maximum inhibition efficiency of 45.49 % with 100 ppm of the inhibitor. The results confirm the correlation between the phytochemical composition and corrosion inhibition capacity.